Erythropoietin regulates immune/inflammatory reaction and improves neurological function outcomes in traumatic brain injury. Issue 11 (3rd October 2017) - Zhou, Zi‐wei; Li, Fei; Zheng, Zhi‐tong; Li, Ya‐dan; Chen, Tong‐heng; Gao, Wei‐wei; Chen, Jie‐li; Zhang, Jian‐ning
Abstract: Introduction: Traumatic brain injury (TBI) remains a leading cause of disability and death among young people in China. Unfortunately, no specific pharmacological agents to block the progression of secondary brain injury have been approved for clinical treatment. Recently, neuroprotective effects of erythropoietin (EPO) have been demonstrated in addition to its principal function in erythropoiesis, and hence it is viewed as a potential drug for TBI. In this study, we have investigated the neuroprotective effects of EPO associated with immune/inflammatory modulation in a mouse experimental TBI model. Methods: EPO (5000 U/kg body weight, i.p.) was injected at 1 hr, 1, 2, and 3 days after TBI, and its effect on cognitive function, brain edema, immune/inflammatory cells including regulatory T cells (Tregs), neutrophils, CD3 + T cells, and microglia, cytokines including interleukin‐10 (IL‐10), transforming growth factor‐β (TGF‐β), interleukin‐1β (IL‐1β), and tumor necrosis factor‐α (TNF‐α) were evaluated at different time points after treatment. Results: EPO treatment significantly decreased brain edema and improved cognitive function when compared to Saline‐treated mice ( p < .05). EPO treatment also significantly increased Tregs level in spleen and injured brain tissue as well as significantly reduced the infiltration and activation of immune/inflammatory cells (neutrophils, CD3 + T cells, and microglia) in the injured hemisphere compared to Saline‐treated control animals ( p < .05). In addition, ELISA analysis demonstrated that EPO treatment increased the expression of anti‐inflammatory cytokine IL‐10, but decreased the expression of proinflammatory cytokine IL‐1β and TNF‐α in the injured brain tissue ( p < .05). Conclusions: These findings suggest that EPO could improve neurological and cognitive functional outcomes as well as regulate immune/inflammatory reaction in TBI. Abstract : EPO attenuated the infiltration and activation of immune/inflammatory cell in the injured brain.